IMPLEMENTATION OF VIRTUAL EDUCATION AND RESISTANCE TO CHANGE IN TEACHERS OF A HIGHER EDUCATION INSTITUTION IN METROPOLITAN LIMA. LIME. 2022. - Alva Miguel, Walter Hugo (2023)
An investigation was carried out whose essential purpose was to establish if the application of the Virtual Education system in the subjects of a Higher Education Institution of Metropolitan Lima has generated resistance to said change in its teaching staff. With this objective, a "descriptive" study was carried out, with a "descriptive-comparative" level, "non-experimental" design with a "quantitative" approach. To this end, the technique known as "survey observation" was applied, applying an instrument elaborated for this purpose, which was previously submitted to the respective processes of validation of its internal and factorial consistency, while reliability was verified by applying the formula de Cronbach. This instrument, thus verified, was applied to a sample of 52 teachers belonging to a Higher Education Institution in Metropolitan Lima. The sample was selected using "non-probabilistic sampling". A "comparison of means" statistical design was assumed and the SPSS version 25 program was used, resorting to the Student's "t" Ratio statistic to verify the hypotheses. The general hypothesis was considered indirectly proven, since the specific hypotheses are an expression of the general hypothesis. The general hypothesis could not be statistically verified because since it is a question of comparing averages with the Reason "t", this procedure has already been carried out based on the three factors, it would have been necessary to incorporate a variable not considered in the approach and therefore not evaluated in the questionnaire.